Huppke–Brendel syndrome: Novel cases and a therapeutic trial with ketogenic diet and N‐acetylcysteine - Šikić, Katarina; Peters, Tessa M. A.; Engelke, Udo; Petković Ramadža, Danijela; Žigman, Tamara; Fumić, Ksenija; Davidović, Maša; Huljev Frković, Sanda; Körmendy, Tibor; Martinelli, Diego; Novelli, Antonio; Lepri, Francesca Romana; et al. (JIMD reports, 2024)
Huppke–Brendel syndrome (HBS) is an autosomal recessive disorder caused by SLC33A1 mutations, a gene coding for the acetyl‐CoA transporter‐1 (AT‐1). So far it has been described in nine pediatric and one adult patient. Therapeutic trials with copper histidinate failed to achieve any clinical improvement. Here, we describe the clinical characteristics of two novel patients, one of them diagnosed by gene analysis and his sib postmortally based on clinical characteristics. We demonstrate a therapeutic trial with acetylation therapy, consisting of N‐acetylcysteine and ketogenic diet, in one of them. We provide biochemical data on N‐acetylated amino acids in cerebrospinal fluid (CSF) and plasma before and after starting this treatment regimen. Our results indicate that ketogenic diet and N‐acetylcysteine do not seem to normalize the concentrations of N‐acetylated amino acids in CSF or plasma. The overall metabolic pattern shows a trend toward lowered levels of N‐acetylated amino acids in CSF and to a lesser extent in plasma. Although there are some assumptions, the function of AT‐1 is still not clear and further studies are needed to better understand mechanisms underlying this complex disorder.